La théorie des prix de transfert internes des grandes sociétés - Copithorne, Lawrence (L'Actualité économique)

(untitled) (HEC Montréal, 1976)
AbstractThere is considerable merit in thinking of the modern multidivisional corporation as an economy within itself. There is an important similarity between the interaction of divisions within a corporation and the perfectly competitive economic model formulated by Leon Walras1. When we look at modern corporations from this viewpoint we discover that much of what we know in general equilibrium economics may have considerable application inside modern corporations. Some of our existing theorems help clarify distinctions between decentralization and central control in corporate management in the same way that they clarify the distinctions between the market economies and those that run by central decree. They help distinguish which divisions must be centrally managed and those which can be left to look after themselves. This viewpoint offers new insights too—that, for instance, the products transferred between divisions may quite logically have two transfer prices instead of one. This viewpoint also permits an easy synthesis of the existing literature on transfer pricing. While the transfer pricing issue is especially important for multinational and international corporations which transfer goods and services between divisions located in different countries, the principles generally apply to any multidivisional corporation. The purposes of this paper are to present a simple, but general analytic model of the multidivisional corporation, to use it to make a synthesis of the existing literature on transfer pricing, and to make some important new discoveries.1 Léon Walras, Elements of Pure Economics, édité et traduit par W. Jaffe (London : George Allen and Unwin, 1954). Kenneth Arrow fait mention de cette similitude dans son article : « Optimization, Decentralization and Internal Pricing in Business Firms », Contributions to Scientific Research in Management, 9-18, Western Data Processing Centre, Los Angeles, University of California Press, 1961.